El greenwashing como estrategia de marketing en Colombia. El caso de la industria textil (2024)
The main objective of this study was to analyze the marketing strategies based on Greenwashing used by the textile industry in Colombia. For this purpose, a review of the current literature on greenwashing was carried out, which allowed the conceptualization and a scale for its identification based on 6 dimensions. Advertising strategies were also analyzed based on 4A marketing and its use in the industry. textile. Using the appropriate theoretical concepts, H&M and Zara advertising campaigns that were identified as greenwashing were analyzed. Finally, consumer reactions to a case of greenwashing that occurred in Colombia (Falabella Colombia's El Denim es + Verde Campaign) were examined with the use of experimental situations. It was evidenced that consumer perception of the brand deteriorated after know the practices identified as greenwashing within an advertising campaign.